Central coherence in adolescents with bulimia nervosa spectrum eating disorders. Issue 5 (22nd August 2014) - Darcy, Alison M.; Fitzpatrick, Kathleen Kara; Manasse, Stephanie M.; Datta, Nandini; Klabunde, Megan; Colborn, Danielle; Aspen, Vandana; Stiles‐Shields, Colleen; Labuschagne, Zandre; Le Grange, Daniel; Lock, James
ABSTRACT Background Weak central coherence—a tendency to process details at the expense of the gestalt—has been observed among adults with bulimia nervosa (BN) and is a potential candidate endophenotype for eating disorders (EDs). However, as BN behaviors typically onset during adolescence it is important to assess central coherence in this younger age group to determine whether the findings in adults are likely a result of BN or present earlier in the evolution of the disorder. This study examines whether the detail‐oriented and fragmented cognitive inefficiency observed among adults with BN is observable among adolescents with shorter illness duration, relative to healthy controls. Method The Rey‐Osterrieth Complex Figure Test (RCFT) was administered to a total of 47 adolescents with DSM5 BN, 42 with purging disorder (PD), and 25 healthy controls (HC). Performance on this measure was compared across the three groups. Results Those with BN and PD demonstrated significantly worse accuracy scores compared to controls in the copy and delayed recall condition with a moderate effect size. These findings were exacerbated when symptoms of BN increased. Discussion Poorer accuracy scores reflect a fragmented and piecemeal strategy that interferes with visual‐spatial integration in BN spectrum disorders. This cognitive inefficiency likely contributes to broad difficulties in executive functioning in this population especially in the context of worsening bulimic symptoms. The findings of this study support the hypothesis that poor global integration may constitute a cognitive endophenotype for BN.